Characteristics of Crosslink Acylation Tapioca Substituted Nagara Beans (Vigna unguiculata spp cylindrica) Flour - Rini Hustiany (Agroindustrial Journal, 2017)
Granules and gels of tapioca will be easily fragile and broken when heated. This study aimed to investigate the characteristics of tapioca cross-linked acylation substituted Nagara bean flour. The method used is the native tapioca cross-linked with Sodium Tripolyphosphat 2 and 5 % and acylated with stearic acid 2 and 4 % under alkaline conditions. Cross-link tapioca then substituted with Nagara beans flour in the ratio 50:50. The highest degree of substitution found in tapioca starch modified with 5 % STPP and 2 % stearic acid, i.e 0.14. The only maximum viscosity of tapioca starch of cross-linked acylation STPP 5 % and stearic acid 2% higher than native tapioca (5220 cP). The breakdown viscosity lower than native tapioca (3651 cP), final and setback viscosity higher than native tapioca (3023 cP and 1454 cP), and pasting temperature higher than native tapioca starch (67.65 °C). When added with Nagara beans flour then the maximum, breakdown, final, and setback viscosity is descended and pasting temperature is 78.5 oC. It is concluded that the granule of tapioca crosslink STTP 5 % and acylation stearic acid 2 % and substituted with Nagara beans flour in the ratio 50:50 is not easily fragile and broken.